TEACHER ATTRITION IN PUBLIC SCHOOLS: A CASE STUDY - Mapula Rebecca MABUSELA; Vimbi Petrus MAHLANGU (International Journal of Social and Educational Innovation)
The purpose of the article was to examine the way female principals experienced teacher attrition in their schools. The purpose about this study was not to generalise but to better understand how female principals experienced teacher attrition. The main question that this article wanted to understand was: What are the causes of teacher attrition in public schools?” The study was conducted in the Tshwane West District of Gauteng Province. The Tshwane West District is one of the fifteen districts of Gauteng Province, situated to the West of Pretoria. Qualitative approach was used, and method of data collected was through interviews. Fourteen (14) female school principals were selected as key informants who could provide information on teacher attrition. Of the fourteen female principals, nine (9) were primary school principals and five secondary school principals. These participants were chosen because they were likely to be knowledgeable and informative about teacher attrition. Analysis: Data was coded, and it was ensured that data that corresponded to the codes which were identified as the analysis was done. Patterns and themes emerged as the coding continued. Then interpretive paradigm was used to understand the participants experiences. It was found that the cause of teacher attrition was due to factors beyond the control of the schools such as legislation, technology, economy, retirement, dismissals, and redundancies in schools.